Assessment of physical fitness of adolescent boys of Northern and Eastern provinces of Sri Lanka using AAHPER fitness test battery - Ketheeswaran, K. (Faculty of Science, University of Ruhuna, 2016)
The aim of the study was to evaluate and compare the American Association for Health Physical Education and Recreation (AAPHER) youth fitness test scores of adolescent boys in Northern and Eastern Province of Sri Lanka. Adolescent boys of 14 years of age from North (n=400) and East (n=400) were randomly selected. AAPHER youth fitness test which included a 50 yard dash for speed, Standing broad jump for explosive power, 1.5 miles run for endurance, sit ups for abdominal strength, shuttle run for agility and pull-ups for arm strength were used. Cumulative score for the test battery was calculated for each participant. Results show that the scores were mostly below 50th percentile in all fitness qualities assessed. It was concluded that the adolescent boys of Northern and Eastern provinces of Sri Lanka have poor physical fitness. Special fitness programs should be designed and implemented to improve the fitness of adolescent with poor fitness. National level common fitness norms should be constructed and standardized for fitness assessment.
Keywords: Adolescent; Fitness; Youths